Effect of Groove Setting for Additional Reinforcement on the Seismic Performance of Precast Shear Wall-slab Joint with No Outer Longitudinal Reinforcement. Issue 1 (February 2020) - Wang, Minling; Guo, Haishan; Qian, Hongliang; Wang, Dongyan; Wang, Huajie
Abstract: The superimposed slab with no outer longitudinal reinforcement at the bottom is a new slab for the assembled shear wall structure, which has a simple detailing and is easier to be transported. To improve the joint performance, the additional reinforcements were often used, but the effect of groove setting at the position of contact between the precast slab and casting slab has not been known clearly. A cyclic loading test was designed and conducted to investigate the influence of groove setting to seismic performance of precast shear wall-slab joint with no outer longitudinal reinforcement. The hysteretic curves and key indexes for the seismic performance of these joints were gained. Also, the influence rule of groove setting to the seismic performance of the joint was studied, and the result showed that groove setting could improve the seismic performance of the joint effectively.